Analysis of effectiveness of in vitro fertilization using vitrificated and native donor oocytes - Mykola Gryshchenko; Andrey Lutskiy (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2018)
Aim: To increase the frequency of pregnancy and delivery rate in in vitro fertilization cycles using native and vitrified donor oocytes. Methods: Analyzing the results of in vitro fertilization in 62 patients who had oocyte donation programs. Patients were divided into 2 groups: the 1st group included 27 women who had used vitrified donor oocytes, and the 2nd group - 35 patients to whom the native oocytes of the donor were used in the in vitro fertilization cycle. The obtained oocytes were vitrified according to the standard technique using the Cryotech Vitrification kit. To prepare the endometrium for the transfer of embryos, a preparatory hormonal therapy regimen was used and the embryos were transferred in a modified menstrual cycle. Results: Studies have shown that the application of the vitrification method in assisted reproductive technology programs allows to achieve clinical results that are not inferior and even significantly exceed the effectiveness of treatment in cycles with native donor oocytes in such parameters as clinical pregnancies, implantation rate and labor. Conclusion: Vitrification is an effective method of cryopreservation of oocytes, which allows to preserve the functional properties of the eggs and, after their fertilization, to obtain embryos with high implantation potential.